Extraction of Spent Bleaching Earth in the Production of Renewable Diesel. Issue 5 (14th April 2015) - Kuuluvainen, Vilppu; Mäki‐Arvela, Päivi; Eränen, Kari; Holappa, Anton; Hemming, Jarl; Österholm, Heidi; Toukoniitty, Blanka; Murzin, Dmitry Y.
Abstract The extraction of oils based on animal fat and vegetable oil from two types of spent bleaching earths, namely from the acidic sepiolite and the nonacidic palygorskite, was investigated by the Soxhlet method with hexane as a solvent. The yields of oil were independent of the feedstock, whereas a much lower oil yield was obtained with palygorskite exhibiting also a smaller surface area as compared to sepiolite which provided a higher yield. The glyceride compositions were very similar in bleached and extracted oils, while slightly lower melting and crystallization energies were determined by differential scanning calorimetry for the extracted oils bleached with acidic clay indicating minor hydrolysis of triglycerides.